Preparation method of immobilized enzyme carrier material for preparing tea polyphenol
By preparing the fixed enzyme carrier material, using the combination of carbon nanotubes and COF materials, combined with the epoxy bond combination of agarose gel, solve the problem of low free ionizing extraction rate and poor stability, and achieve efficient tea polyphenol Extraction and enzyme industrialization application.
Patent Information
- Application Number
- CN202411471404.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when free enzymes are used for tea polyphenol extraction, the extraction rate is low, difficult to recover, and their activity is easily affected by environmental factors, which makes it difficult to store for a long time, hindering the large-scale industrial production and application of enzymes.
Adopt a method of preparing a tea polyphenol spare fixing enzyme carrier material, and the hollow hydroxyl iron powder covered by carbon nanotubes is used to form a nuclear-shell structure to adsorb enzymes and increase the carrier through the COF material to increase the carrier of the carrier through the COF material. Compared with the surface area, combined with the epoxy group bonds of agarose gel to improve the fixing effect of enzymes.
The efficient and fixing of enzymes is achieved, the extraction effect of tea polyphenol is improved, the stability and storage life of enzymes are enhanced, and the industrialization of enzymes is promoted.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tea processing, and in particular relates to a method for preparing an immobilized enzyme carrier material for preparing tea polyphenols. Background Art
[0002] Tea is rich in tea polyphenols, polysaccharides, tea pigments, caffeine and other effective ingredients, among which tea polyphenols are particularly significant, showing a variety of biological activities such as antiviral, antibacterial and antioxidant. At present, the extraction of tea polyphenols from tea mainly uses two methods: solvent extraction and bioenzyme method. However, the solvent extraction method relies on a large amount of organic solvents, has the problems of high risk of solvent residue and high energy consumption, and fails to perform in-depth separation and purification of the extract. In contrast, the bioenzyme method is gradually becoming the research focus in the field of tea polyphenol extraction and separation due to its mild conditions, high extraction rate, low energy consumption and environmentally friendly characteristics. However, free enzymes are currently used, with low extraction rates and difficult to recover. In addition, the activity of free enzymes is easily affected by environmental factors and denatured or inactivated, and it is not easy to store for a long time, which hinders the industrial large-scale production and application of enzymes. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an immobilized enzyme carrier material for preparing tea polyphenols, which is used to solve the technical problems of low extraction rate of free enzyme, difficulty in recovery and difficulty in long-term storage.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0006] S1, mixing ferric oxyhydroxide and ferric chloride solution, stirring, filtering, washing the solid phase, and drying under vacuum at room temperature to obtain material A;
[0007] S2, mixing 4-aminobenzoic acid and deionized water, dispersing by ultrasonic at 50° C., adding the material A, stirring by ultrasonic, filtering, and taking the solid phase to obtain material B;
[0008] S3, mixing the material B, the acidified carbon nanotubes and deionized water, dispersing by ultrasonic at 40° C., filtering, washing the solid phase, and vacuum drying to obtain material C;
[0009] S4, taking trimesaldehyde, dioxane, and acetic acid solution, mixing, stirring, adding 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformylphloroglucinol, and material C, ultrasonically dispersing, and then degassing by freezing pump circulation three times, sealing in a 20 mL glass microwave tube in a nitrogen atmosphere, microwave irradiation, filtering, washing the solid phase, and vacuum drying to obtain material D;
[0010] S5, taking the material D and the acetic acid-sodium acetate buffer solution, mixing, ultrasonically dispersing, adding the complex enzyme, shaking at room temperature, magnetic adsorption separation, washing the solid phase, freeze-drying, and obtaining the material E;
[0011] S6. Mix the material E and agarose gel, stir, let stand, separate by magnetic adsorption, and freeze-dry to obtain the carrier.
[0012] As a preferred technical solution of the present invention, in step S1, the dosage ratio of the ferric oxyhydroxide to the ferric chloride solution is 0.4-0.6 g: 40-60 mL; and the concentration of the ferric chloride solution is 0.18 mol / L.
[0013] As a preferred technical solution of the present invention, in step S2, the mass ratio of 4-aminobenzoic acid, deionized water and material A is 0.22-0.32:25-35:4-6.
[0014] As a preferred technical solution of the present invention, in step S3, the mass ratio of the material B, the acidified carbon nanotubes and the deionized water is 28-32:0.25-0.32:50.
[0015] As a preferred technical solution of the present invention, in step S4, the dosage ratio of trimesaldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformylphloroglucinol, and material C is 1.5-1.7 mg: 1.5-1.7 mL: 2 mL: 35-40 mg: 50-60 mg: 54-58 mg.
[0016] As a preferred technical solution of the present invention, in step S5, the dosage ratio of the material D, acetic acid-sodium acetate buffer solution, and complex enzyme is 2-3g:20-30mL:0.024-0.036g.
[0017] As a preferred technical solution of the present invention, in step S5, the complex enzyme consists of cellulase and pectinase in a mass ratio of 1:1.
[0018] As a preferred technical solution of the present invention, in step S5, the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4 g of sodium acetate and 50 mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting the mixture to 100 mL with deionized water to obtain the acetic acid-sodium acetate buffer solution.
[0019] As a preferred technical solution of the present invention, in step S6, the mass ratio of the material E to the agarose gel is 3-4:5-6.
[0020] Beneficial effects of the present invention:
[0021] The invention discloses a method for preparing an immobilized enzyme carrier material for preparing tea polyphenols. The method comprises the following steps: preparing hollow hydroxy iron powder coated with carbon nanotubes by pitting treatment, which has a good core-shell structure for adsorbing enzyme loads; then coating the surface of the carbon nanotubes with a micro-rough COF material to increase the specific surface area of the carrier, so that the carrier adsorbs more enzymes; and improving the fixation of the enzyme by bonding the nitrogen group of the COF ring structure with the epoxy group on the surface of the agarose gel, so as to obtain an immobilized enzyme carrier material with good tea polyphenol extraction effect. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] Example 1
[0024] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0025] S1. Mix ferric hydroxide and ferric chloride solution, stir for 20 min, filter, wash the solid phase, and dry under vacuum at room temperature for 20 h to obtain material A; the ratio of ferric hydroxide and ferric chloride solution is 0.4 g:40 mL; the concentration of ferric chloride solution is 0.18 mol / L;
[0026] S2, 4-aminobenzoic acid and deionized water were mixed, ultrasonically dispersed at 50°C for 2h, the material A was added, ultrasonically stirred for 12min, filtered, and the solid phase was taken to obtain material B; the mass ratio of 4-aminobenzoic acid, deionized water, and material A was 0.22:25:4;
[0027] S3, take the material B, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 5h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material B, acidified carbon nanotubes, and deionized water is 28:0.25:50; add 150mg of multi-walled carbon nanotubes with a diameter of 20nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer to a blast drying oven at 80°C for drying for 12h, and grind evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0028] S4, take trimesic acid aldehyde, dioxane, acetic acid solution, mix, stir for 20 minutes, add 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, material C, ultrasonically disperse for 30 minutes, then degas three times through a freezing pump cycle, seal in a 20mL glass microwave tube in a nitrogen atmosphere, and use a CEMExporer microwave synthesizer to perform microwave irradiation at 100°C for 3h (microwave power 300W), filter, take the solid phase for washing, and vacuum dry at 100°C for 12h to obtain material D; the dosage ratio of trimesic acid aldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, and material C is 1.5mg:1.5mL:2mL:35mg:50mg:54mg;
[0029] S5. Mix the material D and the acetic acid-sodium acetate buffer solution, disperse them ultrasonically for 20 minutes, add the composite enzyme, shake them at room temperature for 1 hour, separate them by magnetic adsorption, wash the solid phase, and freeze-dry them to obtain material E; the dosage ratio of the material D, the acetic acid-sodium acetate buffer solution, and the composite enzyme is 2g:20mL:0.024g; the composite enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4g of sodium acetate and 50mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting it to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution;
[0030] S6. Mix the material E and agarose gel, stir for 2 h, let stand for 20 h, separate by magnetic adsorption, and freeze-dry to obtain the carrier; the mass ratio of the material E to the agarose gel is 3:5.
[0031] The enzyme activity of the immobilized enzyme was measured to be 5974 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5920 U / g.
[0032] Example 2
[0033] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0034] S1. Mix ferric oxyhydroxide and ferric chloride solution, stir for 25 min, filter, wash the solid phase, and dry under vacuum at room temperature for 25 h to obtain material A; the dosage ratio of the ferric oxyhydroxide and ferric chloride solution is 0.5 g:50 mL; the concentration of the ferric chloride solution is 0.18 mol / L;
[0035] S2, 4-aminobenzoic acid and deionized water were mixed, ultrasonically dispersed at 50°C for 2.5h, the material A was added, ultrasonically stirred for 15min, filtered, and the solid phase was taken to obtain material B; the mass ratio of 4-aminobenzoic acid, deionized water, and material A was 0.27:30:5;
[0036] S3, take the material B, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 5.5h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material B, acidified carbon nanotubes, and deionized water is 30:0.28:50; add 150mg of multi-walled carbon nanotubes with a diameter of 25nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer to a blast drying oven at 80°C for drying for 12h, and grind evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0037] S4, take trimesaldehyde, dioxane, acetic acid solution, mix, stir for 25 minutes, add 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, material C, ultrasonically disperse for 35 minutes, then degas three times through a freezing pump cycle, seal in a 20mL glass microwave tube in a nitrogen atmosphere, and use a CEMExporer microwave synthesizer to perform microwave irradiation at 100°C for 3h (microwave power 300W), filter, take the solid phase for washing, and vacuum dry at 100°C for 12h to obtain material D; the dosage ratio of trimesaldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, and material C is 1.6mg:1.6mL:2mL:38mg:55mg:56mg;
[0038] S5. Mix the material D and the acetic acid-sodium acetate buffer solution, disperse them ultrasonically for 25 minutes, add the complex enzyme, shake them at room temperature for 1.5 hours, separate them by magnetic adsorption, wash the solid phase, and freeze-dry them to obtain material E; the dosage ratio of the material D, the acetic acid-sodium acetate buffer solution, and the complex enzyme is 2.5g:25mL:0.03g; the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4g of sodium acetate and 50mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting it to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution;
[0039] S6. Mix the material E and agarose gel, stir for 2.5 hours, let stand for 25 hours, separate by magnetic adsorption, and freeze-dry to obtain the carrier; the mass ratio of the material E to the agarose gel is 3.5:5.5.
[0040] The enzyme activity of the immobilized enzyme was measured to be 5979 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5927 U / g.
[0041] Example 3
[0042] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0043] S1. Mix ferric oxyhydroxide and ferric chloride solution, stir for 30 min, filter, wash the solid phase, and vacuum dry at room temperature for 30 h to obtain material A; the dosage ratio of the ferric oxyhydroxide and ferric chloride solution is 0.6 g: 60 mL; the concentration of the ferric chloride solution is 0.18 mol / L;
[0044] S2, 4-aminobenzoic acid and deionized water were mixed, ultrasonically dispersed at 50°C for 3h, the material A was added, ultrasonically stirred for 17min, filtered, and the solid phase was taken to obtain material B; the mass ratio of 4-aminobenzoic acid, deionized water, and material A was 0.32:35:6;
[0045] S3, take the material B, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 6h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material B, acidified carbon nanotubes, and deionized water is 32:0.32:50; add 150mg of multi-walled carbon nanotubes with a diameter of 30nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer it to a blast drying oven at 80°C for drying for 12h, and grind it evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0046] S4, take trimesic acid aldehyde, dioxane, acetic acid solution, mix, stir for 30 minutes, add 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, material C, ultrasonically disperse for 40 minutes, then degas three times through a freezing pump cycle, seal in a 20mL glass microwave tube in a nitrogen atmosphere, and use a CEMExporer microwave synthesizer to perform microwave irradiation at 100°C for 3h (microwave power 300W), filter, take the solid phase for washing, and vacuum dry at 100°C for 12h to obtain material D; the dosage ratio of trimesic acid aldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, and material C is 1.7mg:1.7mL:2mL:40mg:60mg:58mg;
[0047] S5. Mix the material D and the acetic acid-sodium acetate buffer solution, disperse them ultrasonically for 30 minutes, add the complex enzyme, shake them at room temperature for 2 hours, separate them by magnetic adsorption, wash the solid phase, and freeze-dry them to obtain material E; the dosage ratio of the material D, the acetic acid-sodium acetate buffer solution, and the complex enzyme is 3g:30mL:0.036g; the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4g of sodium acetate and 50mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting it to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution;
[0048] S6. Mix the material E and agarose gel, stir for 3 hours, let stand for 30 hours, separate by magnetic adsorption, and freeze-dry to obtain the carrier; the mass ratio of the material E to the agarose gel is 4:6.
[0049] The enzyme activity of the immobilized enzyme was measured to be 5977 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5923 U / g.
[0050] Comparative Example 1
[0051] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0052] S1. Mix ferric oxyhydroxide and ferric chloride solution, stir for 25 min, filter, wash the solid phase, and dry under vacuum at room temperature for 25 h to obtain material A; the dosage ratio of the ferric oxyhydroxide and ferric chloride solution is 0.5 g:50 mL; the concentration of the ferric chloride solution is 0.18 mol / L;
[0053] S2, take the material A, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 5.5h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material A, acidified carbon nanotubes, and deionized water is 30:0.28:50; add 150mg of multi-walled carbon nanotubes with a diameter of 25nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer it to a blast drying oven at 80°C for drying for 12h, and grind it evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0054] S3, take trimesic acid aldehyde, dioxane, acetic acid solution, mix, stir for 25 minutes, add 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, material C, ultrasonically disperse for 35 minutes, then degas three times through a freezing pump cycle, seal in a 20mL glass microwave tube in a nitrogen atmosphere, and use a CEMExporer microwave synthesizer to irradiate with microwaves at 100°C for 3h (microwave power 300W), filter, take the solid phase for washing, and vacuum dry at 100°C for 12h to obtain material D; the amount ratio of trimesic acid aldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, and material C is 1.6mg:1.6mL:2mL:38mg:55mg:56mg;
[0055] S4, take the material D and acetic acid-sodium acetate buffer solution, mix them, ultrasonically disperse them for 25 minutes, add the complex enzyme, shake them at room temperature for 1.5 hours, separate them by magnetic adsorption, wash the solid phase, freeze-dry them, and obtain material E; the dosage ratio of the material D, acetic acid-sodium acetate buffer solution, and complex enzyme is 2.5g:25mL:0.03g; the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is mixed with 5.4g of sodium acetate and 50mL of deionized water, adjusted to pH 4.6 with glacial acetic acid, and then diluted to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution;
[0056] S5. Mix the material E and agarose gel, stir for 2.5 hours, let stand for 25 hours, separate by magnetic adsorption, and freeze-dry to obtain the carrier; the mass ratio of the material E to the agarose gel is 3.5:5.5.
[0057] The enzyme activity of the immobilized enzyme was measured to be 5663 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5541 U / g.
[0058] Comparative Example 2
[0059] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0060] S1. Mix ferric oxyhydroxide and ferric chloride solution, stir for 25 min, filter, wash the solid phase, and dry under vacuum at room temperature for 25 h to obtain material A; the dosage ratio of the ferric oxyhydroxide and ferric chloride solution is 0.5 g:50 mL; the concentration of the ferric chloride solution is 0.18 mol / L;
[0061] S2, 4-aminobenzoic acid and deionized water were mixed, ultrasonically dispersed at 50°C for 2.5h, the material A was added, ultrasonically stirred for 15min, filtered, and the solid phase was taken to obtain material B; the mass ratio of 4-aminobenzoic acid, deionized water, and material A was 0.27:30:5;
[0062] S3, take the material B, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 5.5h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material B, acidified carbon nanotubes, and deionized water is 30:0.28:50; add 150mg of multi-walled carbon nanotubes with a diameter of 25nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer to a blast drying oven at 80°C for drying for 12h, and grind evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0063] S4, take the material C and acetic acid-sodium acetate buffer solution, mix them, ultrasonically disperse them for 25 minutes, add the complex enzyme, shake them at room temperature for 1.5 hours, separate them by magnetic adsorption, wash the solid phase, freeze-dry them, and obtain material E; the dosage ratio of the material C, acetic acid-sodium acetate buffer solution, and complex enzyme is 2.5g:25mL:0.03g; the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is made of 5.4g sodium acetate and 50mL deionized water, the pH is adjusted to 4.6 with glacial acetic acid, and then diluted to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution;
[0064] S5. Mix the material E and agarose gel, stir for 2.5 hours, let stand for 25 hours, separate by magnetic adsorption, and freeze-dry to obtain the carrier; the mass ratio of the material E to the agarose gel is 3.5:5.5.
[0065] The enzyme activity of the immobilized enzyme was measured to be 5681 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5558 U / g.
[0066] Comparative Example 3
[0067] A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols comprises the following steps:
[0068] S1. Mix ferric oxyhydroxide and ferric chloride solution, stir for 25 min, filter, wash the solid phase, and dry under vacuum at room temperature for 25 h to obtain material A; the dosage ratio of the ferric oxyhydroxide and ferric chloride solution is 0.5 g:50 mL; the concentration of the ferric chloride solution is 0.18 mol / L;
[0069] S2, 4-aminobenzoic acid and deionized water were mixed, ultrasonically dispersed at 50°C for 2.5h, the material A was added, ultrasonically stirred for 15min, filtered, and the solid phase was taken to obtain material B; the mass ratio of 4-aminobenzoic acid, deionized water, and material A was 0.27:30:5;
[0070] S3, take the material B, acidified carbon nanotubes, and deionized water, mix them, ultrasonically disperse them at 40°C for 5.5h, filter, wash the solid phase, and vacuum dry to obtain material C; the mass ratio of the material B, acidified carbon nanotubes, and deionized water is 30:0.28:50; add 150mg of multi-walled carbon nanotubes with a diameter of 25nm to a mixed acid solution of 15mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and ultrasonically treat them at a temperature of 30°C and a power of 300W for 3h, add 200mL of deionized water, stir evenly with a glass rod, and then stand and settle at room temperature for 24h, filter and separate, wash the solid phase, transfer to a blast drying oven at 80°C for drying for 12h, and grind evenly to obtain the acidified carbon nanotubes; the mass fraction of the concentrated sulfuric acid is 98%, and the mass fraction of the concentrated nitric acid is 68%;
[0071] S4, take trimesaldehyde, dioxane, acetic acid solution, mix, stir for 25 minutes, add 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, material C, ultrasonically disperse for 35 minutes, then degas three times through a freezing pump cycle, seal in a 20mL glass microwave tube in a nitrogen atmosphere, and use a CEMExporer microwave synthesizer to perform microwave irradiation at 100°C for 3h (microwave power 300W), filter, take the solid phase for washing, and vacuum dry at 100°C for 12h to obtain material D; the dosage ratio of trimesaldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformyl phloroglucinol, and material C is 1.6mg:1.6mL:2mL:38mg:55mg:56mg;
[0072] S5. Mix the material D and acetic acid-sodium acetate buffer solution, disperse them ultrasonically for 25 minutes, add the complex enzyme, shake them at room temperature for 1.5 hours, separate them by magnetic adsorption, wash the solid phase, and freeze-dry them to obtain the carrier; the dosage ratio of the material D, acetic acid-sodium acetate buffer solution, and complex enzyme is 2.5g:25mL:0.03g; the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:1; the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4g of sodium acetate and 50mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting to 100mL with deionized water to obtain the acetic acid-sodium acetate buffer solution.
[0073] The enzyme activity of the immobilized enzyme was measured to be 5647 U / g. After being stored at room temperature for 5 days, the enzyme activity was measured to be reduced to 5524 U / g.
[0074] Performance Testing
[0075] Tea leaves were crushed and passed through an 80-mesh sieve to obtain 2 g of powder in a 100 mL beaker. 6 mg of the immobilized enzyme carrier material obtained in Examples 1-3 and Comparative Examples 1-3 and 20 mL of acetic acid-sodium acetate buffer solution with a pH of 4.6 were added. Then, 20 mL of 50% ethanol solution by volume was added. The mixture was enzymolyzed at 50° C. for 90 min and filtered under reduced pressure to obtain a filtrate. The yield of tea polyphenols was measured by ferrous tartrate spectrophotometry. The test results are shown in Table 1 below.
[0076] Table 1
[0077] Tea polyphenols yield (%) Example 1 28.34 Example 2 28.47 Example 3 28.41 Comparative Example 1 24.55 Comparative Example 2 23.89 Comparative Example 3 24.11
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an immobilized enzyme carrier material for preparing tea polyphenols, characterized in that: The following steps are involved: S1, mixing ferric oxyhydroxide and ferric chloride solution, stirring, filtering, washing the solid phase, and drying under vacuum at room temperature to obtain material A; S2, mixing 4-aminobenzoic acid and deionized water, dispersing by ultrasonic at 50° C., adding the material A, stirring by ultrasonic, filtering, and taking the solid phase to obtain material B; S3, mixing the material B, the acidified carbon nanotubes and deionized water, dispersing by ultrasonic at 40° C., filtering, washing the solid phase, and vacuum drying to obtain material C; S4, taking trimesaldehyde, dioxane, and acetic acid solution, mixing, stirring, adding 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformylphloroglucinol, and material C, ultrasonically dispersing, and then degassing by freezing pump circulation three times, sealing in a 20 mL glass microwave tube in a nitrogen atmosphere, microwave irradiation, filtering, washing the solid phase, and vacuum drying to obtain material D; S5, taking the material D and the acetic acid-sodium acetate buffer solution, mixing, ultrasonically dispersing, adding the complex enzyme, shaking at room temperature, magnetic adsorption separation, washing the solid phase, freeze-drying, and obtaining the material E; S6. Mix the material E and agarose gel, stir, let stand, separate by magnetic adsorption, and freeze-dry to obtain the carrier.
2. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S1, the ratio of the ferric oxyhydroxide to the ferric chloride solution is 0.4-0.6 g: 40-60 mL; the concentration of the ferric chloride solution is 0.18 mol / L.
3. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S2, the mass ratio of 4-aminobenzoic acid, deionized water and material A is 0.22-0.32:25-35:4-6.
4. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S3, the mass ratio of the material B, the acidified carbon nanotubes and the deionized water is 28-32:0.25-0.32:
50.
5. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S4, the dosage ratio of trimesaldehyde, dioxane, acetic acid solution, 2,4-diamino-6-phenyl-S-triazine, 2,4,6-triformylphloroglucinol, and material C is 1.5-1.7 mg: 1.5-1.7 mL: 2 mL: 35-40 mg: 50-60 mg: 54-58 mg.
6. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S5, the dosage ratio of the material D, acetic acid-sodium acetate buffer solution, and complex enzyme is 2-3 g: 20-30 mL: 0.024-0.036 g.
7. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S5, the complex enzyme is composed of cellulase and pectinase in a mass ratio of 1:
1.
8. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S5, the acetic acid-sodium acetate buffer solution is prepared by mixing 5.4 g of sodium acetate and 50 mL of deionized water, adjusting the pH to 4.6 with glacial acetic acid, and then diluting the mixture to 100 mL with deionized water to obtain the acetic acid-sodium acetate buffer solution.
9. The method for preparing an immobilized enzyme carrier material for preparing tea polyphenols according to claim 1, characterized in that: In step S6, the mass ratio of the material E to the agarose gel is 3-4:5-6.